Community gardening: Basic psychological needs as mechanisms to enhance individual and community well-being - Quested, Eleanor; Thogersen-Ntoumani, Cecilie; Uren, H.; Hardcastle, Sarah; Ryan, R. (2018)
Community gardens have been associated with a number of positive outcomes, including community and individual well-being. We used self-determination theory as a framework to interpret the social-psychological characteristics of community gardens that may determine their role in sustaining need satisfaction and well-being. Semistructured face-to-face interviews were conducted with 5 experienced community gardeners and 10 aspiring community gardeners. Data were analyzed via a framework approach to thematic analysis. Findings support the proposition that satisfaction of community-level needs may be the precursor to communities and individuals experiencing well-being, via experiences of participating in community gardens. Findings have implications for how community-based interventions could be optimized via targeted integration of theories of motivation and perspectives of well-being.